Exploring the use of manga in translation practice: Insights from Vietnamese tertiary-level EFL lecturers - Thanh Thao, Le; Trut Thuy, Pham (Indonesian Journal of Applied Linguistics, 2024)
This qualitative study explores the perceptions of Vietnamese tertiary-level English as a Foreign Language (EFL) lecturers regarding the use of manga in translation practice. With the growing interest in innovative language teaching methodologies, this research aims to provide insights into how manga, a popular Japanese graphic novel genre, can be integrated into language education to enhance learning experiences. The study involved semi-structured interviews with nine Vietnamese EFL teachers across different career stages, including three novice, three mid-career, and three near-end career teachers, from two educational institutions in Vietnam. A thematic analysis of the interview data revealed three key themes: enhanced engagement and motivation among students when using manga for translation exercises, challenges in maintaining academic rigor, and varied cultural perceptions and receptivity towards manga as a translation tool. Findings indicate that manga can significantly enhance student engagement and motivation, offering a culturally rich and visually appealing medium for language learning. However, challenges in aligning manga content with academic standards and maintaining language accuracy were noted. The study also highlighted diverse cultural attitudes toward the use of manga in educational settings, influenced by generational and pedagogical perspectives. This study contributes to the field of language education by providing empirical insights into the use of manga in translation practice, underscoring the importance of cultural sensitivity and pedagogical balance in incorporating innovative materials in language curriculums. It offers valuable guidance for educators and curriculum designers seeking to enhance language learning experiences through engaging and diverse educational resources.